Distal Pancreatectomy With or Without Splenectomy: Indications, Pitfalls and Long Term Outcomes. Results of A Single Center Consecutive Series of 95 Laparoscopic Distal Pancreatectomies - Damoli, Isacco; Butturini, Giovanni; Daskalaki, Depsoina; Marchegiani, Giovanni; Malleo, Giuseppe; Esposito, Alessandro; Salvia, Roberto; Bassi, Claudio (JOP. Journal of the Pancreas, 2012)
Context There are increasing evidences that spleen preservation is of clinical value for patients undergoing distal pancreatectomy. Laparoscopy appears to increase the rate of spleen preservation through both Warshaw and Kimura techniques. Objective To present early and long term outcomes of a consecutive series of laparoscopic distal pancreatectomies with or without splenectomy and to discuss the pros and cons of spleen preservation. Methods All patients undergone laparoscopic distal pancreatectomy were included in the study. Demographic and clinical characteristics were analyzed. Postoperative complications were prospectively recorded in an institutional database. Long term follow up was assessed by outpatient clinic and direct contact. Follow up ended on May 2012. Results In the Surgical Unit B between May 1999 and December 2011, 95 consecutive patients underwent laparoscopic distal pancreatectomy (76 female, mean age 46.8 years). Conversion rate was 3.2%. En bloc splenectomy was associated in 56 patients (59%). Among 39 patients (41%) with spleen preservation, 9 had a Warshaw procedure. Mortality was nil. Postoperative pancreatic fistula developed in 26% while a re-operation was necessary in 10.5%. In three patients splenectomy was performed during the reoperation. In the long term follow up, 19% of spleen preserving subgroup developed asymptomatic gastric varices. Overall 68% of splenectomized patients adhered to vaccine prophylaxis while one patients who did not, developed a severe sepsis; 13% had a more than 2 years persistent reactive thrombocytosis requiring anti-aggregation therapy. None thromboembolic accident was reported. Conclusion Laparoscopy is a good tool to perform spleen preserving distal pancreatectomy. Spleen preservation per se is a “risk factor” for specific early and late complications with or without splenic vessels sacrifice. Splenectomy leads to an increased risk of infectious and vascular accident adequately preventable by vaccination and anti-aggregation therapy.